THE POPULAR DA’WAH MOVEMENT IN URBAN COMMUNITIES: THE ROLE OF HADRAMI SCHOLARS’ DA’WAH IN RESPONSE TO RELIGIOUS RADICALISM IN INDONESIA - Arif Zamhari; Imam Mustofa (Akademika : Jurnal Pemikiran Islam, 2020)
This article discusses how the role of the scholars of the descendants of Hadrami or known as Habib performs the activities of popular Islamic Preaching (henceforth: da’wah) in the urban community. This paper specifically analyzes the activities of da’wah of Majelis Salawat Ahbabul Mustafa led by Habib Syech, a Habib, a descendant of the Prophet who lived in Solo, Central Java. Recently, a similar da’wah was made by young Habib to gain popularity among the youth in several major cities in Indonesia. By using the media of tambourine instrumental music in reading the Shalawat, the da’wah of Habib Syech successfully attracts the interest of many participants who mostly came from groups of young people. In the middle of the hard blasphemies of the Salafi Preacher (Dai) against the majority of the religious practices of Indonesian Muslims, the Majelis Salawat led by Habib Shaykh conducted the ‘counter attack’ by means of-ways and elegant manners. This group also performs the da’wah through a cultural approach as Walisongo did by using Javanese idioms to get closer to the objects of da'wah which are mostly located in Java. Keywords: Habib, Majelis Salawat, Da’wah, Youth.